The presidential speeches and US-Iran nuclear deal: Franklin D. Roosevelt and John F. Kennedy precepts on freedom, dignity, and independence - Cabrejas-Artola, Cristina (Penerbit Universiti Kebangsaan Malaysia, 2022)
The US-Iran nuclear deal offers a unique opportunity that could potentially change the course of international relations ending decades of offensive yet ineffective foreign policies toward states' harmony. By rebuilding the security in the Middle East as we enter a new multipolar era, the US-Iran nuclear deal will likely determine the future of the world balance of power, in which Iran could tilt the scales. A successful outcome will ensure Iran exits forty-three years of financial, political, military, and technological isolation, consolidating its status as a regional influencer. On the other hand, the US will have the chance to manoeuvre its survival as a superpower despite the gradual expansion control of Russia and China in the Middle East and further afield. Given the continued hiatus of the US's selective memory of what is deemed reasonable and harmful moral judgement when justifying sanctions, we need to consider a more harmonious and diversified worldview paradigm in the international nuclear deal and peace process. Concentration upon current news developments in Vienna and Tehran and, in conjunction with the analogy of the two famous speeches of Franklin D. Roosevelt and John F. Kennedy, this article seeks to demonstrate how these universal principles of freedom, dignity and independence are the underlying factors for the US to remain good moral power but not implemented in the current negotiation with Iran.